"APOPTOSIS COLOR." SCREENING STRATEGY FOR DIAGNOSIS EARLY STAGES OF PRIMARY OPEN-ANGLE GLAUCOMA - M. A. Kovalevskaya; M. I. Sergeeva (Oftalʹmologiâ, 2017)
Purpose: to develop a screening strategy for the early diagnosis of primary open-angle glaucoma.Patients and Methods: 1 group — 250 patients with suspected glaucoma (42–75 years), 2 — 250 with the 1st stage primary open-angle glaucoma (42–61), 3 — 3,000 healthy persons (35 to 50). Surveys: visometry, tonometry iCare, biomicroscopy, gonioscopy, pachymeria, ophthalmoscopy with a high dioptric lens of 60 D, standard automated perimetry of the SITA-Standard and SITA-SWAP program, assessing the color sensitivity according to the Famsworth-Munsell 100 HueTes method.Results: 1 group — SITA-SWAP: MD -2,55±0,7 dB, PSD 2,46±1,15 dB. Mansell test: TES = 58.6±18.7 (p<0.05), average level of color recognition; mild deficiency of color vision — 41–100 TES; by the RGB system: colors of the first order; tone in RGB (0–239): blue — 160; HCV: blue — 240; range of wavelengths: blue — 440–485 nm; frequency: blue — 620–680 THz. 2 group — on SITA-SWAP: MD — 5,13±1,3 dB, PSD 2,58±0,9 dB. Mansell test: TES = 86,9±21,8; average level of color recognition; mild deficiency of color vision; single deviations in the system of blue (azure, blue, blue); color I order (blue), III order (blue, azure); tone in RGB — (0–239): blue (azure, blue) — 140, blue — 160; HCV — blue (azure, blue) — 210, blue — 240; range of wavelengths: 450–500 nm (blue — 485–500, blue — 440–485); frequencies: 600–680 THz (blue — 600–620, blue — 620–680). Control group — SITA-SWAP within the norm, Mansell test: TES = 40,1±17,3 (p<0.05), medium level of color recognition, lack of color vision absent / mild, single deviations.Conclusion: in patients with glaucoma suspicion, the score of errors was higher than in the control group with Munsell test. In patients with glaucoma, the number of errors is greater than in patients with suspected glaucoma, and 2.2 times higher than in the control group.